Transcriptional Regulation of Divergent Capsule Biosynthesis and Transport Operon Promoters in Serogroup B Neisseria meningitidis - Tzeng, Yih-Ling (American Society for Microbiology, 2001)
The clinically important serogroups B, C, Y, and W-135 of Neisseria meningitidis produce sialic acid capsules that are critical in pathogenesis. In each of these serogroups, the capsule transport (ctrABCD) and capsule biosynthesis (synABCD) operons are divergently transcribed from putative promoters located in a 134-bp intergenic region (J. S. Swartley, J. H. Ahn, L. J. Liu, C. M. Kahler, and D. S. Stephens, J. Bacteriol. 178:4052–4059, 1996). In this study we further assessed the role of the intergenic sequence in the transcriptional regulation of the sialic acid capsules of N. meningitidis. Insertional mutagenesis or deletions of the 134-bp sequence in the serogroup B meningococcal strain NMB resulted in a marked reduction or elimination of ctrABCD and synABCD transcription, with a concomitant loss of encapsulation. Chromosomal transcriptional lacZ-ermC reporter fusions of syn and ctr promoters were constructed through allelic exchange. Using these constructs, both operons were found to be constitutively transcribed in meningococci, the biosynthesis operon about fourfold higher than the transport operon. Both promoters showed increased activity during stationary-phase growth. In addition to the promoters, a 70-bp 5′ untranslated region (UTR) upstream of synA was found to have a direct repeat and an inverted repeat that overlapped three putative integration host factor binding sites. Mutation of this 70-bp UTR and of the direct repeat upregulated both syn and ctr transcription. Regulation through the synA UTR was absent in a K1 Escherichia coli strain that produces identical capsular polysaccharide, implicating species-specific regulation. Meningococcal sialic acid capsule expression is initiated by divergent promoters in a 134-bp intergenic region, is repressed at the transcriptional level by the 5′ UTR of synA, is increased during stationary-phase growth, and shows species-specific regulation. Transcriptional regulation is another important control point for sialic capsule expression in N. meningitidis.